2022
DOI: 10.1002/cl2.1271
|View full text |Cite
|
Sign up to set email alerts
|

Technology‐based and digital interventions for intimate partner violence: A systematic review and meta‐analysis

Abstract: Background A growing body of research shows the promise and efficacy of technology‐based or digital interventions in improving the health and well‐being of survivors of intimate partner violence (IPV). In addition, mental health comorbidities such as anxiety, post‐traumatic stress disorder (PTSD), and depression occur three to five times more frequently in survivors of IPV than non‐survivors, making these comorbidities prominent targets of technology‐based interventions. Still, research on the long‐term effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 186 publications
(576 reference statements)
0
7
0
1
Order By: Relevance
“…Fifteen reviews with Demographic domain interventions were identified (Asgary, Emery, & Wong, 2013;Branco, Altafim, & Linhares, 2021;Chen & Chan, 2016;Drew, Morgan, Pollock, & Young, 2020;Efevbera, McCoy, Wuermli, & Betancourt, 2018;Emezue, Chase, Udmuangpia, & Bloom, 2022;Fang, Barlow, & Zhang, 2022;Goldstein, Rosen, Howlett, Anderson, & Herman, 2020;Linde et al, 2020;Rivas et al, 2015;Spencer, Stith, & King, 2021;Stephens-Lewis et al, 2021;Van Parys, Verhamme, Temmerman, & Verstraelen, 2014;Waid, Cho, & Marsalis, 2022;Walsh, Zwi, Woolfenden, & Shlonsky, 2015). Examples of demographic determinants of mental health include age and gender.…”
Section: Demographic Domainmentioning
confidence: 99%
“…Fifteen reviews with Demographic domain interventions were identified (Asgary, Emery, & Wong, 2013;Branco, Altafim, & Linhares, 2021;Chen & Chan, 2016;Drew, Morgan, Pollock, & Young, 2020;Efevbera, McCoy, Wuermli, & Betancourt, 2018;Emezue, Chase, Udmuangpia, & Bloom, 2022;Fang, Barlow, & Zhang, 2022;Goldstein, Rosen, Howlett, Anderson, & Herman, 2020;Linde et al, 2020;Rivas et al, 2015;Spencer, Stith, & King, 2021;Stephens-Lewis et al, 2021;Van Parys, Verhamme, Temmerman, & Verstraelen, 2014;Waid, Cho, & Marsalis, 2022;Walsh, Zwi, Woolfenden, & Shlonsky, 2015). Examples of demographic determinants of mental health include age and gender.…”
Section: Demographic Domainmentioning
confidence: 99%
“…En la siguiente pregunta se describe la implementación de la Taxonomía NANDA, NIC y NOC en el ámbito hospitalario en todo el mundo, haciendo una comparación entre los diferentes países con más estudios o publicaciones como: España, Corea del Sur, México y Brasil pertenecientes a diferentes continentes (7,(23)(24)(25)(26)(27)(28)(29) En España se hallaron estudios que evidencian su implementación, ya que este país tiene mayor relevancia por ser pionero en la creación y de la redacción de las primeras publicaciones de NANDA, NIC y NOC; pero actualmente todavía en ese país los estudios recientes manifiestan que la taxonomía NANDA sigue siendo criticada por la posible complejidad en el procedimiento, la falta de tiempo para realizarlo y la falta de conocimientos del personal, aun así se destaca la importancia y valor en el despistaje de problemas prevalentes, además de cuidados e intervenciones necesarias (8,29,30). Por otra parte, en el Continente Asiático como Corea del Sur su aplicación ha sido de gran impacto y en la actualidad aquel país donde es constante el desarrollo de nuevas tecnologías, la implementación y uso en los hospitales cuentan con un sistema informático estandarizado, que enlaza directamente estos lenguajes enfermeros, reduciendo el tiempo de selección de datos y permitiendo a las enfermeras muchas ventajas para atención directa (31)(32)(33)(34).…”
Section: Rq2: ¿La Aplicación Del Lenguaje Enfermero Mejora La Gestión...unclassified
“…Furthermore, no subgroup analysis was conducted regarding the reduction in IPV, nor were intervention intensity, delivery mode, intervention setting, or control group characteristics investigated in subgroup analysis; yet, research suggests that these factors may influence the effectiveness of psychosocial interventions for IPV survivors (Arroyo et al, 2017; Hameed et al, 2020). Since 2019, the research field has expanded significantly, particularly with the exploration of numerous digital interventions for IPV survivors (Emezue et al, 2022).…”
Section: Introductionmentioning
confidence: 99%